"No days off": Using self-determination theory to better understand workaholism in National Collegiate Athletic Association Division I coaches - Tolentino, K., Readdy, T.; Raabe, J. (Journal of Clinical Sport Psychology, 2024)
Workaholism (i.e., working excessively and compulsively) is associated with negative physical, psychological, and social consequences. Researchers have previously examined antecedents of workaholism, but the experiences of sport coaches have not yet been investigated. This study explored (a) differences in National Collegiate Athletic Association Division I coaches` workaholism, as well as need satisfaction and frustration based on gender, coaching role, gender of athletes coached, age, and years of coaching experience; and (b) how coaches` perceptions of their three basic psychological needs are associated with tendencies to work excessively and compulsively. A total of 873 National Collegiate Athletic Association Division I coaches participated in the research. Data analyses revealed significant differences in participants` workaholism as well as need satisfaction and frustration. Structural equation modeling indicated a significant relationship between reported levels of workaholism and perceptions of the three needs. Findings illustrate the importance of basic psychological needs in preventing coaches` workaholism and maintain optimal functioning.